Telaah Potensi Antivirus Mitraginin terhadap Protease 3CLpro SARS-CoV-2 dengan Pendekatan Molecular Docking - Setiawansyah, Arif; Susanti, Gita; Hidayati, Nurul; Gemantari, Baiq Maylinda; Alrayan, Reza; Hadi, Ismanurrahman; Luthfiana, Dewi; Hasanah, Nurul (Universitas Hamzanwadi, 2024)
SARS-CoV-2 is a novel coronavirus identified as a major caused of COVID-19. COVID-19 can be prevented and managed by preventing the SARS-CoV-2 infection through inhibition of SARS-CoV-2 main protease. Mitragynine is one of the major compounds found in Mitragyna speciosa leaves that has the potential to be developed as an anti-COVID-19 agent. This research was implemented to evaluate that potential by observing the molecular interaction of mitragynine with the essential amino acid residues of SARS-CoV-2 3CLpro. The study was undertaken by in silico method via molecular docking approach using Autodock 4.2. The potential of mitragynine in inhibiting the SARS-CoV-2 main protease was justified based on its free binding energy and Ki. The result revealed that mitragynine exhibited a lower free binding energy and Ki than remdesivir with the free binding energy and Ki value of -7.80 kcal/mol dan 1.92 µM dan -7.41 kcal/mol dan 3.72 µM, respectively. This concluded that mitragynine has the potential as a SARS-CoV-2 main protease inhibitor with the affinity was better than remdesivir. However, further in vitro research must be carried out to prove this potential.